Football Training Like the Pros: Get Bigger, Stronger, and Faster Following the Programs of Today's Top Players - Smith Chip (McGraw -Hill, 2007)
Are you ready to go hard core? Then let top performance trainer Chip Smith break you down and build you up into the biggest, baddest player on the field. The number-one expert pros turn to when they want to get pumped and primed for the season and the first choice of aspiring players when they need to take their game to the next level, Smith coaches the best of the best at his state-of-the-art training center, Competitive Edge Sports. Now in Football Training Like the Pros, he brings his once-exclusive top training secrets to you.